Synthesis and PVP Coating Effects on Cadmium Ferrites for Antibacterial Applications - Sami, We'am; Khadayier, Abdulhussain A.; Shaheed, Mohamed A. (Iraqi Journal of Science, 2026)
This work focuses on the effect of coating with polyvinylpyrrolidone on the structure and morphology of synthesized powdered cadmium ferrites through the microwave-assisted combustion method. Antibacterial activities test of Cd-ferrite before and after coating with PVP for Escherichia coli and Staphylococcus aureus were also studied. Structure and impurity phases characterizations, surface morphology with chemical composition analysis, as well as lattice vibrations determined by XRD analysis, field emission scanning electron microscopy with energy dispersive X-ray spectroscopy, and foruier transform, exhibited spinel structure with crystallite size decreasing with coating with polyvinylpyrrolidone from 21.23nm to 19.71nm. The images recorded by field emission- scanning electron microscopy showed that polyvinylpyrrolidone plays a very important role in preventing Cd-ferrite agglomeration. The presence of Fe-O bonds from Cd-ferrite was observed in the FT-IR spectra. Antibacterial activity was found to be enhanced with the coating of cd-ferrite.